Efforts and challenges in adopting international financial reporting standards (IFRS) in Nigeria (Journal of Business Management and Accounting, 2012)
Financial reporting in emerging and developed economies has been a challengingdebate, due to the frequent changes as well as updates on accounting rules andregulations. Nigeria, being an emerging economy has witnessed a dramatic changeand improvement on the accounting reporting since after political development ofthe country in 1960. The establishment of Nigerian Security Exchange (NSE) in 1982and the establishment of Nigerian Accounting Standard Board (NASB) in 1984 by theInstituteof Chartered Accounting of Nigeria (ICAN) who were the pioneer legislationson the road map to financial reporting in Nigeria. Even though laws and regulationswere also issued by the regulatory bodies in Nigeria to ensure quality(value relevance)financial reporting, the level of compliance with the regulations have been very lowas reported by the World Bank in the 2004 and 2011(ROSC report). Subsequently,professionals, regulatory bodies and government made the first effort by establishingthe road map and the World Bank committee for the adoption of the InternationalFinancial Reporting Standards (IFRS) in 2010. Secondly, the formation of the FinancialReporting Council (FRC) in 2011 and FRC training institute in 2012. However, theseefforts by the government, World Bank and regulators were faced with the challenges onthe development of regulatory and legal framework as well as training of professionalsand regulators on the new accounting standard (IFRS). Therefore, this paper explorestwo main issues:(i) the efforts of government, professional bodies, and regulatoryagencies by providing accounting framework and trainings; and (ii) challenges inadopting IFRS due to weaknesses of SAS and unethical behaviours of the preparers offinancial statements.